2017
DOI: 10.21605/cukurovaummfd.383225
|View full text |Cite
|
Sign up to set email alerts
|

Şekerbulak (Diyadin-Ağrı) Dolaylarında Yüzeyleyen Volkanik Kayaçların Mineralojik-Petrografik ve Jeokimyasal Özellikleri

Abstract: Bu çalışma, Ağrı ilinin yaklaşık 40 km güneydoğusunda yer alan Şekerbulak dolaylarında yüzeyleyen volkanik kayaçların mineralojik-petrografik ve jeokimyasal incelenmesini konu almaktadır. Bölgede plütonik ve volkanik birimler gözlenmektedir. Plütonik birimleri tonalit, granodiyorit, monzogranit ve granit türü kayaçlarda oluşan ve Taşlıçay Granitoidi olarak tanımlanan granitoidler temsil etmektedir. Volkanik birimler ise Yeltepe Trakiandeziti ve Yuva Riyoliti'dir. Bu birimler subalkali, kalkalkali, yüksek K'lu … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…This researcher suggested that the volcanism in the region started in the alkaline character and then ended with Süphan volcanites, which showed calc-alkaline character. Açlan and Turgut (2017) stated that plutonic and volcanic units are observed around Şekerbulak (Ağrı). They said that the plutonic units were represented by Taşlıçay Granitoid consisting of tonalite, granodiorite, monzogranite and granite.…”
Section: Introductionmentioning
confidence: 99%
“…This researcher suggested that the volcanism in the region started in the alkaline character and then ended with Süphan volcanites, which showed calc-alkaline character. Açlan and Turgut (2017) stated that plutonic and volcanic units are observed around Şekerbulak (Ağrı). They said that the plutonic units were represented by Taşlıçay Granitoid consisting of tonalite, granodiorite, monzogranite and granite.…”
Section: Introductionmentioning
confidence: 99%